The important role of co-infections in patients with AIDS and progressive disseminated histoplasmosis (PDH) : A cohort from Colombia (2018)
A total of 23/45 (51%) patients with AIDS and histoplasmosis from Medellín, Colombia had other infections. Tuberculosis was the most common (n = 16/23, 70%). Pneumocystosis and cryptococcosis were found in three patients each (13%), bacterial infection and cytomegalovirus occurred each in two patients (9%) while toxoplasmosis, herpes virus and esophageal candidiasis were recorded in one patient each (4%). Of all co-infected patients, 18/23 (78%) had one, four (17%) had two and one (4%) had three additional opportunistic infections. © 2017 The Author(s)